Heterosexual ally development in counseling psychologists: experiences, training, and advocacy for the LGBT community - Asta, Elizabeth L., author; Vacha-Haase, Tammi, advisor; Banning, Jim, committee member; Bloom, Larry, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2011)
When focusing on advocacy for minority rights, it is beneficial to explore the role allies play in advocating for and supporting their peers. Thus, the purpose of this study was to examine how counseling psychologists working in university counseling settings conceptualize their ally work, as well as how their counseling psychology training impacted their ally development. This study was guided by the tradition of phenomenological qualitative study, and constant comparison analysis served as the strategy for inductive analysis. Pre-doctoral interns and senior staff psychologists, who self-identified as heterosexual, were interviewed regarding their experiences and development with ally work. Results indicated that there is wide variation regarding how psychologists view the ally experience, but that individuals find common meaning, challenges, and training experiences within their ally development. In particular, results showed a predominant need for increased training in social justice advocacy and LGBT support within counseling psychology training programs.
Keywords: advocacy; ally; counseling psychologists; heterosexual; training; university counseling centers